Anterolateral Ligament Reconstruction Protects the Repaired Medial Meniscus: A Comparative Study of 383 Anterior Cruciate Ligament Reconstructions From the SANTI Study Group With a Minimum Follow-up of 2 Years. Issue 8 (July 2018) - Sonnery-Cottet, Bertrand; Saithna, Adnan; Blakeney, William G.; Ouanezar, Herve; Borade, Amrut; Daggett, Matt; Thaunat, Mathieu; Fayard, Jean-Marie; Delaloye, Jean-Romain
Background: The prevalence of osteoarthritis after successful meniscal repair is significantly less than that after failed meniscal repair. Purpose: To determine whether the addition of anterolateral ligament reconstruction (ALLR) confers a protective effect on medial meniscal repair performed at the time of anterior cruciate ligament reconstruction (ACLR). Study Design: Cohort study; Level of evidence, 3. Methods: Retrospective analysis of prospectively collected data was performed to include all patients who had undergone primary ACLR with concomitant posterior horn medial meniscal repair through a posteromedial portal between January 2013 and August 2015. ACLR autograft choice was bone–patellar tendon–bone, hamstring tendons (or quadrupled hamstring tendons), or quadrupled semitendinosus tendon graft with or without ALLR. At the end of the study period, all patients were contacted to determine if they had undergone reoperation. A Kaplan-Meier survival curve was plotted, and a Cox proportional hazards regression model was used to perform multivariate analysis. Results: A total of 383 patients (mean ± SD age, 27.4 ± 9.2 years) were included with a mean follow-up of 37.4 months (range, 24-54.9 months): 194 patients underwent an isolated ACLR, and 189 underwent a combined ACLR + ALLR. At final follow-up, there was no significant difference between groups in postoperative side-to-side laxity (isolated ACLR group, 0.9 ± 0.9 mm [min to max, –1 to 3]; ACLR + ALLR group, 0.8 ± 1.0 mm [min to max, –2 to 3]; P = .2120) or Lysholm score (isolated ACLR group, 93.0 [95% CI, 91.3-94.7]; ACLR + ALLR group, 93.7 [95% CI, 92.3-95.1]; P = .556). Forty-three patients (11.2%) underwent reoperation for failure of the medial meniscal repair or a new tear. The survival rates of meniscal repair at 36 months were 91.2% (95% CI, 85.4%-94.8) in the ACLR + ALLR group and 83.8% (95% CI, 77.1%-88.7%; P = .033) in the ACLR group. The probability of failure of medial meniscal repair was >2 times lower in patients with ACLR + ALLR as compared with patients with isolated ACLR (hazard ratio, 0.443; 95% CI, 0.218-0.866). No other prognosticators of meniscal repair failure were identified. Conclusion: Combined ACLR and ALLR is associated with a significantly lower rate of failure of medial meniscal repairs when compared with those performed at the time of isolated ACLR.